Gubernamentalidad y agua : Analíticas del poder en el desierto de Atacama (2017)
Can the political philosophy proposed by Michel Foucault contribute to the understanding, explanation and transformation of the current water crisis in northern Chile? Reviewing the Foucaultian concept of governmentality, the article intends to contribute to the enrichment of a critical theoretical framework in order to notice how, in the context of neoliberal capitalism, large corporations and mega-projects are intervening in the destruction of specific and microterritorial ecosystems of Chile, taking as a specific case the Atacama desert and the water issue.The main interest is to examine how the concept of governmentality helps to understand the modalities assumed by the exercise of power, one of them being political governments that normalize situations of deterioration of nature. The case of water in the Atacama region, Chile will be specifically discussed.